FIRING ANGLE OPTIMIZATION TO MAXIMIZE TORQUE PRODUCTION AND MINIMIZING TORQUE RIPPLE ON 5 KW 12/8 TYPE SWITCHED RELUCTANCE MOTOR USING GENETIC ALGORITHM - Hidayat, Syahadatul
This final project discusses the optimization of turn on ?on and turn off ?off angles to control a 5 kW 12/8 Switched Reluctance Motor (SRM) by employing multi-objective Genetic Algorithm (GA). The optimization objectives are to maximize torque production while minimizing the ensued torque ripple. Finite Element Analysis (FEA) is utilized to obtain the SRM’s static flux linkage and torque characteristics. The static characteristics are then used as the basis of SRM drive model for the firing angles (?on and ?off) optimization process. Based on the optimized firing angles obtained from the multi-objective optimization, the SRM’s performaces are characterized over a wide range of operating region. It has been found that by using the optimized firing angles the SRM can achieve rated power at 3000 rpm with current command of 90 A. A light electric vehicle (e-Trike) model also developed to estimate the capabilities of the said SRM and proposed control using the optimized firing angles.